MODELING AND SIMULATION FOR ANALYSIS AND IMPROVEMENT OF A SOCK MANUFACTURING SYSTEM IN A MICRO-ENTERPRISE - Caballero Morales, Santiago Omar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
The productivity of the national sock manufacturing industry in Mexico has been affected by the introduction of large foreign manufacturers. Nevertheless there is a small sector formed by micro and small enterprises which is competing for the national market. Commonly these enterprises are informally planned and managed as the entrepreneurs have very basic knowledge of accounting, manufacturing-production practices and local market behavior. In this situation the use of computer-assisted modeling and simulation can be a cost-effective tool to support their planning and managerial decisions. The main objective of this research is to provide a methodology to analyze a standard sock manufacturing system and support the decision making process to improve its performance by means of modeling and simulation. The methodology to build the model of the manufacturing system consists of statistical representations of processing times, arrival description of raw material, identification of resources and dependencies. The model is statistically validated and simulation is performed for analysis of resource utilization and estimation of profits. This analysis led to designing an alternative model which presented a significant increase in production and higher profits. It is expected that this work can be used as a reference to guide academic practitioners and entrepreneurs to analyze and improve managerial decisions for similar manufacturing processes in developing economies.